Removal of ammonium ions from aqueous solutions using electrodialysis - Petrychenko, Alona; Makarenko, Iryna; Radovenchyk, Iaroslav; Shabliy, Tetyana (Eastern-European Journal of Enterprise Technologies, 2018)
We report results of investigating the processes of electrochemical oxidation of ammonium in a two-chamber electrolyzer depending on the composition of the original solutions ‒ anolyte and catholyte, current density, electrolysis duration. It is shown that the electrochemical oxidation of ammonia in aqueous solutions of ammonium sulfate proceeds at a rate of 14‒55 mg/(dm3·hours) at a current density of 86.2‒172.4 A/m2 and the starting concentrations of a given ion of 10‒120 mg/dm3. The rate of ammonium oxidation under these conditions increases with increasing starting concentrations of ammonium and with increasing current density. The output of oxidized ammonium for current and specific consumption of electricity for water purification from ammonium are defined based on ammonium concentrations and current density and increase with an increase in the concentration of a given ion and a decrease in current density. Ammonium oxidation rate increases by 1.66 times in solutions of ammonium sulfate ([NH4+]=90 mg/dm3, j=172.4 A/m3) in tap water, compared with distilled water. This is due to the presence of chlorides in tap water, which act as a catalyst during ammonium oxidation at the expense of the intermediate formation of active chlorine. Under these conditions, we observed complete oxidation of ammonia compared with solutions on distilled water where the residual ammonium concentrations reach 1‒3 mg/dm3. It is shown that the presence of chlorides in catholyte at a concentration of 30 mg/dm3 almost does not accelerate the oxidation of ammonium. Our work demonstrated thatекек in all cases, during oxidation of ammonium, pH of solutions decreases to 6.1‒2.0, which is predetermined by the oxidation of ammonium to nitrates and the acidification of water by the formed nitric and sulphuric acids. Based on the reported results, it can be concluded that the electrochemical method is the most promising method for the extraction of ammonium ions from water. Its application makes it possible to achieve a 100 % water purification.